Live virus vaccination of pediatric solid organ transplant candidates within 1 month prior to transplantation: A multicenter experience. Issue 4 (13th July 2021) - Rosenthal, Ayelet; Madigan, Theresa; Chen, Sharon F.; Gans, Hayley; Nadimpalli, Sruti
Abstract: Background: Solid organ transplant (SOT) recipients are at increased risk of vaccine‐preventable illness due to the high degree of immunosuppression required following transplantation. The current recommendation is to vaccinate with live attenuated vaccines, including Measles, Mumps, and Rubella (MMR) and Varicella (VAR) vaccines, at least 4 weeks prior to transplant. However, data to support the time interval between vaccine and transplant are limited. Methods: We conduct a literature review of the natural history of the viruses and length of viremia following live‐attenuated viral vaccines, and we describe a series of 5 cases from 2 pediatric transplant centers in which live attenuated viral vaccines were administered within 21 days prior to SOT. Results: None of the 5 children who received MMR or VAR 8‐21 days prior to liver (2) and heart (3) transplant suffered from vaccine‐related viral illness after transplant, even in the presence of significant immunosuppression with T‐cell‐depleting agents. Conclusion: These cases support that shorter intervals of live vaccine administration prior to transplant may be safe, allowing the vaccination of a larger cohort of SOT candidates. Increasing pretransplant vaccinations is crucial since, in most cases, live viral vaccines are contraindicated posttransplantation, and the most effective vaccine approaches utilize prime‐boost strategies, priming before and boosting after transplant.